Strategi Daya Dukung dari Jasa Ekosistem Wisata Muara Angke dengan Menggunakan SWOT dan IFAS-EFAS - Isti Susanti; Endang Hilmi; Sudarmalik Sudarmalik (MAIYAH, 2022)
Mangrove Ecotourism in Muara Angke has the natural attractions as tourist destinations in Jakarta. The sustainability of tourism function is an important role to support the economic development. This research aimed to determine the socio-economic characteristics of visitors and the carrying capacity to support the formulating analysis of ecotourism development strategies. The study used a survey method and deep interview. The results showed that the score of PPC < RCC > ECC indicated that the carrying capacity didn’t exceed the limitation conservation (has opportunity to developed). The development strategy were (1) the maintain the natural panorama of mangrove forests to support ecotourism activity; (2) The maintain fishing tourism activities; (3) the developing the instagramable photo spots; (4) The building canteens/food court that provides processed mangrove products; (5) Increasing the cost retribution to maintain the sustainability of environmental functions; (6) Involve the local communities to support ecotourism development